Brainstem auditory evoked response in normal term neonates - Laura M. F. F. Guilhoto; Virgínia S. Quintal; Maria T. Z. da Costa (Arquivos de Neuro-Psiquiatria)
Brainstem auditory evoked response (BAER) is a reliable test for neonatal auditory and neurological dysfunction and it permits early diagnosis and rehabilitation. The purpose of this study is to demonstrate latencies of BAER in normal term neonates in order to obtain reference values in a university hospital. BAER was performed in the second day of life in 47 normal newborns (25 male, 22 female) which gestational ages were higher than 37 and lower than or equal to 40 weeks that did not present familial history of deafness. The exam was performed with 80 dBHL alternating polarity 10/sec clicks presented monaurally. Two thousand stimulus trials were averaged and duplicated for each ear. Mean wave latencies in msec was: I, 1.79 (SD 0.20); II, 2.88 (SD 0.28); III, 4.54 (SD 0.31); IV, 5.86 (SD 0.36); V, 6.75 (SD 0.38); inter-peak latencies (IPL) I-III, 2.75 (SD 0.36); IPL III-V, 2.22 (SD 0.22); and IPL I-V, 4.97 (SD 0.43).